Analisis Faktor Risiko Low Back Pain Pada Perawat Di Tempat Kerja Menurut Ecological Models (Literature Review) - Martha Sri Astuti; M. Bagus Qomaruddin; Oedojo Soedirham (UNIVERSITAS MUHAMMADIYAH SURABAYA, 2022)
Objective: to identify risk factors of low back pain on Nurses in the workplace according to Ecological Models.Methods: The research design is Literature Review using Preferred Reporting Items for Systematic Review and Meta Analysis (PRISMA) checklist. Systematic search was done in Scuence Direct, Medline, Pubmed, and Proquest. The articles was searched using keywords and cross-sectional, RCT, Quasi-experimental, Analisa kuantitatif, Prospective longitudinal study, Randomized Control and Trial. Results: 41 study were included in this review. The study found 14 ris factors in intrapersonal level, 2 in interpersonal level, 4 in organizational level and 4 in community level. The study found that smoking is not a risk factor.Conclusion: The study found 24 risk factors for low back pain on nureses in the workplace in 4 levels of Ecological Models. A comprehensive intervention is needed to get more effective result.